The Influence of School Principals' Leadership, Work Motivation and Work Discipline on the Performance of State High School Teachers in The City of Bima - Mahfud, Mahfud; Hermanto, Hermanto; Noviyanti, Mery (Universitas Islam Negeri Sultan Syarif Kasim Riau Pekanbaru, 2024)
The aim of this research is to analyze and describe the influence of school principal leadership, work motivation and discipline on the performance of public high school teachers in Bima City. This research is an associative quantitative research with a research population of public high school teachers in Bima City of 448 people, and 22% or 100 people were used as research samples using random sampling techniques. The research instrument is a questionnaire developed from each variable. The research data analysis technique uses multiple linear regression analysis. The results of the research show that the principal's leadership, work motivation and work discipline have a positive and significant partial and simultaneous influence on the performance of public high school teachers in Bima City. This research illustrates that in efforts to improve the quality of teachers, it is necessary to improve the quality of school principals, motivation and work discipline